Using Estill Voice Training in the middle school choral rehearsal - McEathron, Danielle (My University, 2026)
For my research I am interested in how the Estill Voice Training (EVT) can be used in the middle school choral rehearsal to help students better understand and use their vocal mechanism. What originally drew me to EVT was the focus on the anatomy of the voice. Often a voice teacher will ask a student to do something abstract with their voice this can leave the singing feeling like they are shooting in the dark to try to figure out what exactly is being asked of them. This is not to say that illustrative language has no place in vocal pedagogy, but that we as vocal instructors need to make sure we are tying that illustrative language to the physical vocal mechanism. For example, instead of saying “try that again but with a darker sound, like you’re a 45-year-old opera singer” I would say, “try that again but with a darker sound, keep your resonance forward but feel like you are yawning.” This gives the voice students something tangible they can manipulate and feel in their instrument. This project consists of two lessons where students are introduced to the Estill Voice Training method, explore three different vocal covers in warm-ups, then receive feedback in repertoire rehearsal that is based in EVT. My first lesson plan focuses on introducing EVT to my students and experimenting with a few different EVT styles including sob, speech and twang. In the next lesson plan, during repertoire rehearsal I will use feedback based in EVT to address any issues that arise in rehearsal. For the final lesson plan, we will use our repertoire to experiment with body covers, or different styles covered in EVT. This includes the different vocal styles students experiment with in the first lesson; sob, speech and twang. When I started teaching EVT was something I wanted to include in my pedagogy but I was unsure how to take this method used in individual voice lessons and transfer it to the middle school ensemble. In the past I have used EVT sparingly in warm-ups and when rehearsing repertoire but this project will help me find what EVT methods or tools work in my classroom so I can better incorporate them in my day to day teaching. My goal is to empower young vocal students to better understand and use their voice as not only an instrument but a muscle. During my time at Kansas State I have developed in my conducting and my rehearsal pacing. Being able to practice conducting in front of other music teachers and two master conductors really inspired me to be reflective of my conducting and make changes if a gesture is not working with my ensemble. After taking Theories of Music Teaching and Choral Rehearsal Techniques I have started planning more varied activities with a faster pace. Before I would stick to a very clear but simple regiment of warm-up, repertoire, and the occasional music theory or listening activity. But, after my time at Kansas State I am more adventurous in my lesson plans and try to include movement, and composition activities as well as more strategies to improve the sound of my choirs like singing through straws or singing in circles around the room.
Keywords: Estill Voice Training; Middle School Choir; Choral Rehearsal